DOP056 Efficacy and safety of anti-fractalkine monoclonal antibody, E6011, in patients with Crohn's disease who had lost response to anti-TNFα agents: A multicentre, open-label, Phase 1/2 study. (16th January 2018) - Matsuoka, K; Naganuma, M; Tanida, S; Kitamura, K; Matsui, T; Arai, M; Fujiya, M; Horiki, N; Nebiki, H; Kinjo, F; Miyazaki, T; Matsumoto, T; et al.
Abstract: Background: Fractalkine (FKN)/CX3CL1 represents a new type of leukocyte trafficking regulator, which signalling via its receptor CX3CR1 on leukocytes allows them to migrate directly to effector sites during inflammation. We have assessed the safety of E6011, a humanised anti-FKN monoclonal antibody, in multiple ascending dose (MAD) cohorts and long-term extension in patients with Crohn's disease (NCT02039063). We have also evaluated preliminarily the efficacy and target occupancy of E6011 in the patients. Methods: Patients with mild to moderate disease (150≤CDAI<450) who had lost of response to conventional therapy including anti-TNFα were sequentially allocated into one of four dose cohorts (2, 5, 10, and 15 mg/kg) and received E6011 intravenously every 2 weeks for 12 weeks. The patients who showed a clinical response or remission at week 12 could receive the same doses in an extension period for up to 40 weeks. Two-target quasi-steady-state (QSS) model was applied for describing the profile of serum E6011 and total FKN concentration in the patients. Results: Twenty-eight patients were enrolled in the MAD cohorts; 2 mg/kg ( n = 6), 5 mg/kg ( n = 8), 10 mg/kg ( n = 7) and 15 mg/kg ( n = 7). Twenty-seven (96%) had failed previous treatment with anti-TNFα. Adverse events (AEs) were reported in 18 (64%) patients during 12 weeks. All were mild or moderate. The most common AE was viral upper respiratory tract infection ( n = 5). Serious AEs (SAEs) were Crohn's diseases ( n = 2) and anaemia ( n = 1). All SAEs were considered not related to the study drug. Serum E6011 concentration increased nonlinearly with dose and the trough levels reached a steady state after around 6 weeks. Anti-drug-antibodies were developed in four (14%) patients at week 12. An exploratory simulation indicated that E6011 treatment resulted in high binding occupancy on membrane-bound FKN and inhibition of free circulating FKN level in the patients. Overall, CR70 (CDAI decrease ≥ 70), CR100 (CDAI decrease ≥ 100) and clinical remission (CDAI < 150) were observed at week 12 in 10/25 (40%), 9/25 (36%) and 4/25 (16%) patients who had basal CDAI ≥ 220, respectively. After the MAD cohorts of 2, 5, and 10 mg/kg, a total of nine patients entered the extension period. During the extension, AEs were observed in 8 (89%) patients and the most common AE was viral upper respiratory tract infection. Four SAEs were reported; Crohn's disease ( n = 3) and miscarriage of partner ( n = 1). Of the patients with basal CDAI≥220 who entered the extension, 4/7 (57%) patients showed a sustained CR70 or clinical remission at week 52. Conclusions: E6011 has been shown to be safe and well-tolerated in the patients with Crohn's disease. Blocking FKN/CX3CR1 interaction could provide a potentially novel approach for therapy of Crohn's disease.